Christian faith and Greek philosophy in late antiquity : essays in tribute to George Christopher Stead, Ely Professor of Divinity, University of Cambridge (1971-1980), in celebration of his eightieth birthday, 9th April 1993 - Stead, Christopher.; Wickham, Lionel R.; Hammond Bammel, Caroline P. (Vigiliae Christianae, Supplements, 1993)
This volume is a collection of thirteen essays offered in dedication to Professor C.G. Stead on his 80th birthday. Their theme is the philosophy underlying the presentation of Christian teaching in Late Antiquity. The essays deal with individual theologians (Augustine, Ambrose, Dionysius the Areopagite, Gregory of Nyssa), with ideological background (Christian and Roman universalism), and with the discussion of particular texts. A bibliography and brief appreciation of Professor Stead's contribution to Patristic studies are included.